Polygenic architecture and cardiovascular risk of familial combined hyperlipidemia. (January 2022) - Trinder, Mark; Vikulova, Diana; Pimstone, Simon; Mancini, G.B. John; Brunham, Liam R.
Abstract: Background and aims: Familial combined hyperlipidemia (FCHL) is one of the most common inherited lipid phenotypes, characterized by elevated plasma concentrations of apolipoprotein B-100 and triglycerides. The genetic inheritance of FCHL remains poorly understood. The goals of this study were to investigate the polygenetic architecture and cardiovascular risk associated with FCHL. Methods and results: We identified individuals with an FCHL phenotype among 349, 222 unrelated participants of European ancestry in the UK Biobank using modified versions of 5 different diagnostic criteria. The prevalence of the FCHL phenotype was 11.44% (n = 39, 961), 5.01% (n = 17, 485), 1.48% (n = 5, 153), 1.10% (n = 3, 838), and 0.48% (n = 1, 688) according to modified versions of the Consensus Conference, Dutch, Mexico, Brunzell, and Goldstein criteria, respectively. We performed discovery, case-control genome-wide association studies for these different FCHL criteria and identified 175 independent loci associated with FCHL at genome-wide significance. We investigated the association of genetic and clinical risk with FCHL and found that polygenic susceptibility to hypercholesterolemia or hypertriglyceridemia and features of metabolic syndrome were associated with greater prevalence of FCHL. Participants with an FCHL phenotype had a similar risk of incident coronary artery disease compared to participants with monogenic familial hypercholesterolemia (adjusted hazard ratio vs controls [95% confidence interval]: 2.72 [2.31–3.21] and 1.90 [1.30–2.78]). Conclusions: These results suggest that, rather than being a single genetic entity, the FCHL phenotype represents a polygenic susceptibility to dyslipidemia in combination with metabolic abnormalities. The cardiovascular risk associated with an FCHL phenotype is similar to that of monogenic familial hypercholesterolemia, despite being ∼5x more common. Graphical abstract: Image 1 Highlights: Genome-wide association studies of familial combined hyperlipidemia identified 175 single-nucleotide variants at a genome-wide threshold for significance. Familial combined hyperlipidemia displays strong genetic correlations with features of apolipoprotein B-containing lipoproteins. Individuals with a polygenic susceptibility to hypercholesterolemia or hypertriglyceridemia and metabolic risk factors have the highest risk of familial combined hyperlipidemia. Familial combined hyperlipidemia and familial hypercholesterolemia are associated with similar risk of coronary artery disease, but familial combined hyperlipidemia is at least 5x more common.